2005
DOI: 10.1136/jnnp.2004.039875
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine and related genetic polymorphisms in Down's syndrome IQ

Abstract: Objective: Down's syndrome (DS) is the most frequent genetic cause of Alzheimer-type dementia. Its metabolic phenotype involves an increased trans-sulphuration of homocysteine. The aim of the present study was to investigate the influence of homocysteinaemia (t-Hcys), folate, vitamin B 12 , and related polymorphisms on intelligence quotient (IQ) in DS. Methods: The IQ of 131 patients with trisomy 21 from a specialist centre in Sicily was determined and classified according to DMS-IV. The effects of age, folate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
4
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 34 publications
2
40
4
1
Order By: Relevance
“…Several studies failed to confirm reduced Hcy concentrations in DS patients (11,25,26). Furthermore, in a study with elderly DS patients, Licastro et al (27) observed that their plasma Hcy was higher and their folate lower than in controls; blood concentrations of vitamin B12 were also lower in DS patients than in controls.…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies failed to confirm reduced Hcy concentrations in DS patients (11,25,26). Furthermore, in a study with elderly DS patients, Licastro et al (27) observed that their plasma Hcy was higher and their folate lower than in controls; blood concentrations of vitamin B12 were also lower in DS patients than in controls.…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…Elevated Hcy concentrations may be harmful since they have been associated with elevated risk of cardiovascular disease, neurodegenerative disorders, psychiatric disorders, and decline of cognitive performance (13,25,38). Guéant et al (25) observed that a lower intelligence quotient was associated with higher Hcy concentrations in DS patients, and this association was also observed in the presence of the MTHFR 677T allele alone and in combination with the transcobalamin 776G polymorphic allele.…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…One gene variant in particular, the C677T/C677T genotype, of the 5,10 methylenetetrahydrofolate reductase (MTHFR) gene, has been associated with Down syndrome as well as being a risk factor for other complex congenital anomalies (Botto and Yang, 2000). Moreover, a recent study reported an association between MTHFR and intelligence quotient in patients with Down syndrome (Gueant et al, 2005). The variant form of MTHFR codes for a thermolabile enzyme with reduced activity and has been linked to elevated plasma homocysteine levels in C677T individuals under conditions of folate deficiency (Frosst et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In Down syndrome patients carrying three copies of CBS, the plasma homocysteine level increased with age. Various studies of Down syndrome children showed consistently decreased plasma homocysteine levels compared with the same age controls [20][21][22]31], while trisomy 21 adults showed no difference in homocysteine levels [23], and elderly patients even had increased homocysteine levels compared with controls [32]. Thus the correlation between CBS −4673 genotypes and plasma homocysteine level during embryonic development cannot be truly reflected in the tested undergraduate students.…”
Section: Discussionmentioning
confidence: 92%